PENGEMBANGAN MEDIA PEMBELAJARAN VIDEO ANIMASI ”DUNIA RAHASIA TUMBUHAN” BERBASIS AI UNTUK MENINGKATKAN PEMAHAMAN SISWA PADA PEMBELAJARAN IPAS KELAS IV SDN TLOGOSARI KULON 04 - Prita Iswa Salma; Husni Wakhyudin; Arfilia Wijayanti (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This study is motivated by the low level of students’ understanding of the plant material in the IPAS subject for Grade IV students at SDN Tlogosari Kulon 04. This is due to the lack of engaging learning media, which leads to students being less active during the learning process. Therefore, it is necessary to develop instructional media that can help students comprehend the material and actively participate in learning. One proposed solution is the use of an AI-based animated video learning media titled "Dunia Rahasia Tumbuhan" ("The Secret World of Plants"). With this media, students are expected to more easily grasp the lesson content, thereby achieving learning objectives more effectively. This research employs a Research and Development (R&D) method with a one-group pretest-posttest design. The population consists of all Grade IV students of SDN Tlogosari Kulon 04 in the 2024/2025 academic year, with a sample of 28 students selected using a non-probability sampling technique. Data collection techniques include interviews, observation, tests, and documentation. The results of expert validation from the first material and media expert showed an average score of 86.8%, the second expert 97.3%, and a classroom teacher scored it at 92%, all categorized as “Excellent.” The overall average validation score was 92%. Data analysis showed an improvement in students’ understanding after using the AI-based animated video. Based on the N-Gain effectiveness test, the average score was 0.7813 or 78%, classified as “Effective.” It can be concluded that the AI-based animated video "The Secret World of Plants" effectively improves Grade IV students’ understanding of plant material.